A sensitive bacterial-growth-based test reveals how intestinal Bacteroides meet their porphyrin requirement. Issue 1 (December 2015) - Halpern, David; Gruss, Alexandra
Abstract Background Bacteroides sp. are dominant constituents of the human and animal intestinal microbiota require porphyrins (i.e., protoporphyrin IX or iron-charged heme) for normal growth. The highly stimulatory effect of porphyrins onBacteroides growth lead us to propose their use as a potential determinant of bacterial colonization. However, showing a role for porphryins would require sensitive detection methods that work in complex samples such as feces. Results We devised a highly sensitive semi-quantitative porphyrin detection method (detection limit 1-4 ng heme or PPIX) that can be used to assay pure or complex biological samples, based onBacteroides growth stimulation. The test revealed that healthy colonized or non-colonized murine and human hosts provide porphyrins in feces, which stimulateBacteroides growth. In addition, a common microbiota constituent, Escherichia coli, is shown to be a porphyrin donor, suggesting a novel basis for intestinal bacterial interactions. Conclusions A highly sensitive method to detect porphyrins based on bacterial growth is devised and is functional in complex biological samples. Host feces, independently of their microbiota, andE. coli, which are present in the intestine, are shown to be porphryin donors. The role of porphyrins as key bioactive molecules can now be assessed for their impact onBacteroides and other bacterial populations in the gut.